The time course of recovery of indirect markers of exercise-induced muscle damage induced by multi- and single-joint exercises - Pompermayer, M. G.; Radaelli, R.; Brusco, C. M.; Baroni, B. M.; Cadore, E. L.; Lopez, P.; Reischak-Oliveira, A.; Pinto, R. S. (Sport Sciences for Health, 2021)
Purpose Strength training is performed using multi-joint (MJ) or single-joint (SJ) exercises; however, it is not clear whether different time of recovery is necessary between the two types of exercise. The aim of the present study was to compare the time course of recovery of indirect markers of exercise-induced muscle damage (EIMD) in the elbow flexors after performing MJ and SJ exercises.